¿Development or ‘bien vivir’? Rethinking the social role of the Intercultural University from the questioning of the Educational Effect - Olivera Rodríguez, Inés (2014)
The educative institution is the result of a modern-colonial socialorder determined by a euro-centric knowledge that responds to the logic of capitalism as a world order of power. the debates about schooling that understands its function as the efficient insertion of individuals into society are proof of this. In the order of current public policies, the logic of human development still rules over the national educative projects. this problem worsens when one considers intercultural contexts once the logic of capital, productivity, and economic growth are not the base of other ways of seeing the world. Interculturality as a dialogue and interaction of different symbolic universes demands the incorporation of other epistemologies and schooling logics. Thus, mexican Intercultural universities demand new responses from the formal educative system. these proposals seem to approximate to the construction of plural societies, capable of including everybody in life projects. the purpose is the construction of a true dialogue between forms of knowledge. therefore, the main question that is asked here is: how can educative effects be thought in an intercultural context? to answer it, I have made a critical reading of Anibal Quijano’s theory of the coloniality of power which gives an understanding of interculturality based on the real inclusion of other epistemologies that allow seeing the world from other angles and other forms of knowledge.